HRM readjustment dynamics of an industrial transplant: The case of Toyota in India - Kunju Kunju Mathew, Sagi; Jones, Robert; James, Reynold (2009)
This paper uses a case study of Toyota to analyse the transfer and hybridisation of lean production in a major motor vehicle manufacturing company located in India. Particular emphasis is placed on the dynamics of re-adjustment in relation to HRM practices. Using primary and secondary data in the form of interviews and company documentation, the paper traces the transplantation trajectory of the company over the ten year period between 1999 and 2009. Findings reveal that due to a range of contradictions in the initial configuration of the transplant the company undertook a sequential range of re-adjustment measures involving four strategies: localisation, imitation, hybridisation, and customisation. Several propositions are advanced with the aim of hypothesising which strategies are more likely to be successful in certain contextual situations.